Using the Leadership Quality Concept in the Employees of Municipal Enterprises Selection (Economic journal of Lesya Ukrainka Volyn National University, 2017)
In the article author researched the problems of communal enterprises employees selection.Author proved the expediency of concept of leadership qualities application in the organization of selection. Author researched the individual stages of selection, the methods used at these stages and ways of integrating leadership qualities concept. To simplify the integration of the concept of leadership qualities, approaches to their classification are given.
Keywords: selection of employees, human resources management, communal enterprises, leadership qualities